1998
DOI: 10.1136/gut.43.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their inhibitors in gastric cancer

Abstract: Background-The matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMPs) are strongly implicated in tumour invasion and metastasis. Aims-To investigate the presence of individual MMPs and TIMPs in gastric cancer. Methods-The presence of MMP-1, MMP-2, MMP-3, MMP-9, TIMP-1, and TIMP-2 was identified in a group of gastric cancers (n=74) by immunohistochemistry using monoclonal antibodies. These antibodies were eVective on formalin fixed, paraYn wax embedded sections. Results-A la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 31 publications
8
112
2
1
Order By: Relevance
“…TIMP-1 is a ubiquitous glycoprotein capable of inhibiting all activated collagenases (Gomez et al, 1997). Tissue inhibitor of metalloproteinases were previously found not to be correlated with tumour stage, histological type, lymph node status or survival in human gastric cancer (Murray et al, 1998). We did not find any relation of TIMP-1 372C4T with gastric carcinoma, protein level or survival of the patients.…”
Section: Discussioncontrasting
confidence: 77%
“…TIMP-1 is a ubiquitous glycoprotein capable of inhibiting all activated collagenases (Gomez et al, 1997). Tissue inhibitor of metalloproteinases were previously found not to be correlated with tumour stage, histological type, lymph node status or survival in human gastric cancer (Murray et al, 1998). We did not find any relation of TIMP-1 372C4T with gastric carcinoma, protein level or survival of the patients.…”
Section: Discussioncontrasting
confidence: 77%
“…We observed that co-culture with H. pylori stimulated AGS cell secretion of MMP-1, an important MMP identified within ulcer lesions (28,70). Because type I and III collagens predominate in gastric mucosa (29,44), and both are susceptible to MMP-1, (45), these data suggest a mechanism for H. pyloriinduced gastric stromal destruction.…”
Section: Discussionmentioning
confidence: 79%
“…Murray et al demonstrated that MMP-1 protein immunolocalized in carcinoma cells correlated with a poor prognosis in colorectal (Murray et al, 1996) and oesophageal carcinoma (Murray et al, 1998b), but not in gastric carcinoma (Murray et al, 1998a). However, in oesophageal carcinoma, the significance was minute regarding the prognosis and this report included 19 squamous cell carcinomas which showed only 3 cases (16%) of positive immunostaining of MMP-1 (Murray et al, 1998b).…”
Section: Discussionmentioning
confidence: 89%